Associations of hypertension, diabetes and heart disease risk with body mass index in older Chinese adults: a population-based cohort study - Gordon G Liu; Haoxiang Lin; Meng Liu; Nan Xiao; Shujun Lin (BMJ Open)
Objective Obesity is a well-established risk factor for disease. Controversy exists regarding the relative risk of morbidity and mortality in individuals who are overweight or underweight compared with individuals with a normal body mass index (BMI). In this study, we investigated the associations between BMI and three non-communicable diseases (hypertension, diabetes and heart disease) in older adults.Design Cohort study.Setting This study used data from the China Health and Retirement Longitudinal Study. The baseline survey was carried out in 2011, and follow-up surveys were conducted in 2013, 2015 and 2018.Participants Participants who reported having no doctor-diagnosed chronic disease at baseline were included in this study.Main outcome measures We analysed the association between baseline BMI and disease incidence using Cox proportional hazards models. Disease information included self-reported diagnosed conditions. BMI was categorised according to the standard Chinese criteria: underweight (<18.5 kg/m2), normal body weight (18.5–23.9 kg/m2), overweight (24.0–27.9 kg/m2) and obese (≥28.0 kg/m2).Results A total of 5605 participants were included at baseline. Based on the Kaplan-Meier estimation, the participants who were obese had the highest incidence of all three diseases. Compared with normal weight participants, overweight participants had a greater disease incidence (log-rank tests are p<0.01). Cox regression models showed that with increasing BMI, the HRs of diseases increased accordingly (eg, for hypertension, compared with the BMI group <18.5 kg/m2, the HRs for the BMI groups 18.5–23.9, 24.0–27.9 and ≥28.0 were 1.43 (95% CI 1.00 to 2.05), 2.19 (95% CI 1.51 to 3.18) and 2.89 (95% CI 1.91 to 4.36), respectively).Conclusion A higher BMI was associated with an increased risk of hypertension, diabetes and heart disease in the population aged 45 years and older. Even within normal BMI ranges, a higher BMI was associated with an increased risk of disease. Actions are urgently needed at the population level to address the growing public health challenge of excess weight in the context of an ageing population.